Vasopressin marker copeptin and the development of renal and metabolic disorders in patients with type 2 diabetes - A. Nesen; K. Savicheva; P. Semenovykh; V. Galchiskaya (Український Журнал Нефрології та Діалізу, 2022)
Abstract. The aim of the study was to evaluate the possibility of using copeptin as a marker of renal and metabolic dysfunction in patients with type 2 diabetes.